2012
DOI: 10.3949/ccjm.79a.11133
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: Evolving treatment for a complex disease

Abstract: The cutaneous manifestations of psoriasis can vary in morphology and severity, and therapy should be tailored accordingly. Biologic agents are important new options for treating patients with the most severe forms of the disease. All physicians should be aware that severe psoriasis may increase cardiovascular morbidity and the risk of death, and preventive strategies for patients with severe disease should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…Chronic inflammatory skin diseases, such as atopic dermatitis, psoriasis and rosacea are characterized by the dysregulation of cutaneous innate immunity and an increased incidence of bacteremia (24). Dysfunction of cathelicidin LL-37, a molecule proven to play a central role in innate cutaneous immunity, is expressed in all three of these diseases (25).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammatory skin diseases, such as atopic dermatitis, psoriasis and rosacea are characterized by the dysregulation of cutaneous innate immunity and an increased incidence of bacteremia (24). Dysfunction of cathelicidin LL-37, a molecule proven to play a central role in innate cutaneous immunity, is expressed in all three of these diseases (25).…”
Section: Discussionmentioning
confidence: 99%
“…There are many different hormonal phases throughout a woman's lifetime and the first symptoms of psoriasis can be seen at any time, that is, in childhood, menarche, pregnancy, during hormonal contraceptive use, and menopause [12]. The severity of psoriasis may fluctuate or be influenced by each phase and this relationship can be seen as disease frequency seems to peak during puberty, postpartum, and menopause, when hormone levels fall, while symptoms improve during pregnancy, a state when hormone levels are increased [13, 14]. Recent studies have shown that female hormones significantly affect the biological and immune changes in the skin [15].…”
Section: Introductionmentioning
confidence: 99%
“…При приеме препарата у 15% пациентов наблюдалось повышение уровня триглицеридов в сыворот-ке крови и у 3% -гиперхолестеринемия, причем эти изме-нения в липидном профиле исчезали сразу же после прекра-щения терапии [17]. Кроме того, лечение ЦС может ослож-няться головной болью (15% случаев), парестезиями (7%), гипертрихозом (6%) и мышечно-скелетными болями (5%) [17,34].…”
Section: общие принципы лечения псаunclassified